The state and the multinationals. Possible consequences of the 2008 crisis on power balance (2019)
This research aims to analyze the changes on the Multinational Corporations capacity of action over the States, in order to illustrate the economic and political panorama that arose since the 2008 economic and financial crisis. This is analyzed taking into account the dynamic relation between States and Multinationals and the use of an approach that combines historical and contemporary aspects. Both provide a thesis which harmonizes the variables (such as employment, impact on GDP, mobility and capital international markets) that modify the incidence on companies and, that appear as the main sources of liability of Multinational Corporations in their negotiating processes with the States. Finally, this study reviews the State capitalism as a phenomenon that values the existent role of current economies and, presents the relations between specific cases and their performance.